Contrasting stability of fungal and bacterial communities during long-term decomposition of fungal necromass in Arctic tundra - Andrea Moravcová; Florian Barbi; Camelia Algora; Gabriele Tosadori; Petr Macek; Jana Albrechtová; Petr Baldrian; Petr Kohout (Environmental Microbiome)
Abstract Decomposition is a crucial process in terrestrial ecosystems, driving nutrient cycling and carbon storage dynamics. Considering the amount of fungal necromass produced in soils annually, its decomposition represents an important nutrient recycling process. Understanding the decomposition dynamics and associated microbial communities of fungal necromass is essential for elucidating ecosystem functioning, especially in environmentally sensitive regions such as the Arctic tundra, which remain under-explored. In a three-year field experiment conducted in the Svalbard archipelago, we investigated the decomposition of two types of fungal necromass with differing biochemical properties. We studied the decomposition rate, changes in chemical composition, and the succession of fungal and bacterial communities associated with the decaying fungal necromass. We discovered that up to 20% of fungal necromass remained even after three years of decomposition, indicating that the decomposition process was incomplete. Our results indicate the crucial role of Pseudogymnoascus in decomposing low-quality, highly melanized necromass with a high C:N ratio in Arctic soils, underscoring its importance in carbon cycling in the Arctic tundra. Notably, we observed dynamic changes in bacterial communities, with increasing richness over time and a shift from copiotrophic to oligotrophic species specializing in decomposing recalcitrant material. Our study indicates the strong potential that fungal necromass can play in carbon sequestration of arctic soils and reveals the distinct dynamics between rather stable fungal and rapidly changing bacterial communities associated with the decomposing fungal necromass in the Arctic tundra. These findings enhance our understanding of microbial succession during decomposition in extreme environments and highlight the potentially differing roles of fungi and bacteria in these processes.